DETERMINANTS OF HUMAN PAPILLOMA VIRUS VACCINE HESITANCY AMONG PRIMARY HEALTHCARE WORKERS IN KANO MUNICIPAL LOCAL GOVERNMENT AREA, KANO, KANO STATE - Suberu, Ahmed; Rabi, Uba Mahmoud; Bello, Umar Lawal; Abdullahi, Mohammed Nasiru (FUDMA JOURNAL OF SCIENCES, 2025)
Cervical cancer remains a significant public health burden in low- and middle-income countries, where HPV vaccination programs are limited. Healthcare worker (HCW) hesitancy is a critical barrier to vaccine acceptance and uptake. In Nigeria, cervical cancer is the second most frequent cancer among women aged 15 to 44 with over 14,000 new diagnoses and more than 20 deaths daily. This study utilized mixed research design. The quantitative employed descriptive survey design. For the qualitative study, heads of various immunization units from the selected PHC’s were purposively selected for key informant interview. The study was conducted among 143 primary healthcare workers in Kano Municipal LGA from 10 PHCs selected using a multi-stage sampling technique. The findings from the study revealed that majority of respondents (72.7%) reported that advice from family or friends influenced their decision to get vaccinated, whereas peer recommendations had minimal impact (4.9%). Three themes emerged from the qualitative study: Knowledge gaps and training needs, promoting vaccine acceptance and Willingness to recommend the HPV vaccine. The study concludes that there are significant barriers to vaccine hesitancy such as cost concerns, perceived vaccine efficacy, and limited access to vaccination services. It is recommended to implement targeted educational and accessibility interventions to overcome barriers and enhance HPV vaccine uptake.